Synergetic remineralization effectiveness of calcium, phosphate and fluoride based systems in primary teeth. Issue 1 (April 2017) - Arafa, Abla
Abstract: Objective: To assess remineralization of primary teeth enamel under the presence of fluoride, calcium and phosphorous ions using microhardness and surface roughness testing. Design: Artificial caries lesions were created in enamel surface of 144 human primary molars. Specimens were randomly assigned according to remineralizing agent into six groups: 1) Artificial saliva, 2) Fluoride varnish, 3) Clinpro™white varnish, 4) Relief, 5) Tooth Mousse Plus, 6) Vanish XT TM. Surface micro-hardness and surface roughness were evaluated at baseline, after demineralization, after 2 and 4 weeks remineralization and after exposure to acid challenge. Results: All test groups showed superior results to the control. The surface micro-hardness of Clinpro™ group by 4 weeks remineralization showed statistically the highest value with the least softening as exposed to acid challenge. Concomitantly, by 4 weeks remineralization, Clinpro™ agent was able to regain enamel surface roughness incomparable to that of baseline value statistically the least of test groups. Conclusion: Calcium-phosphate and fluoride remineralizing systems possess added remineralization potency in comparison to artificial saliva. Clinpro™ varnish showed the greatest remineralizing action and the least softening by acid challenge.